Fire Management Analysis at Ahmad Dahlan University Yogyakarta - Subhan ZulArdi; Yudha Dhamar Prasetyo (Periodicals of Occupational Safety and Health, 2025)
Background: Fire management is a systematic series that includes prevention, countermeasures, and post-fire rehabilitation. The fire incident due to an electrical short circuit that occurred in the practicum room of Campus 4 of Ahmad Dahlan University (UAD) shows that fire risk management has not been optimal, especially related to institutional policies. This study aims to analyze the implementation of fire management at Ahmad Dahlan University Yogyakarta. The research used a qualitative descriptive design with a phenomenological approach and was carried out on Campus 1 to Campus 5 of UAD. Informants were selected by purposive sampling. Method: Data collection was carried out through in-depth interviews, field observations, and analysis of related documents, with instruments in the form of interview guidelines and documentation. Data analysis includes data reduction, categorization, narrative presentation, and conclusion drawn, while data validity is ensured through triangulation of techniques and sources. Results: The results of the study show that at the prevention stage, UAD already has organizations and procedures, coaching and training programs, fire protection systems, fire inspections, and hazard control. However, a formal fire and hazard identification policy is not yet available. At the countermeasures stage, UAD already has a fire emergency response team involving security officers on each campus. Meanwhile, at the rehabilitation stage, post-fire investigation and reporting activities have been carried out, but the official fire audit has not been carried out. Conclusion: It is concluded that fire management at Ahmad Dahlan University has been partially operational, but it still needs policy strengthening, formal hazard identification, and fire audits to achieve a comprehensive fire management system.